Impact of Solid Particle Concentration and Liquid Circulation on Gas Holdup in Counter-Current Slurry Bubble Columns - Sadra Mahmoudi; Mark W. Hlawitschka (Fluids)
In this study, in a three-phase reactor with a rectangular cross-section, the effects of liquid circulation rates and solid particle concentration on gas holdup and bubble size distribution (BSD) were investigated. Air, water, and glass beads were used as the gas, liquid, and solid phases, respectively. Different liquid circulation velocities and different solid loads were applied. The results demonstrate that increasing solid content from 0% to 6% can decrease gas holdup by 50% (due to increased slurry phase viscosity and promotion of bubble coalescence). Also, increasing the liquid circulation rate showed a weak effect on gas holdup, although a slight incremental effect was observed due to the promotion of bubble breakup and the extension of bubble residence time. The gas holdup in counter-current slurry bubble columns (CCSBCs) was predicted using a novel correlation that took into account the combined effects of solid concentration and liquid circulation rate. These findings are crucial for the design and optimization of the three-phase reactors used in industries such as mining and wastewater treatment.